Embedded Mechatronics System Design for Uncertain Environments : Linux®-based, Rasbpian®, ARDUINO® and MATLAB® xPC Target Approach - Chin, Cheng Siong (IET control, robotics and sensors series, 2018)
The book has been prepared for the needs of those who seek an application on developing embedded mechatronics system easy for control purposes. The choice of material is guided by the basic objective of making an engineer or student capable of dealing with embedded system design. The book can be used as a textbook, reference book, laboratory exercise for a first course in Linux®-based embedded system, xPC-Target, PIC-Microchip, ARDUINO®, and Raspberry Pi. The contents of the book are organized into seven main chapters with program codes. The main chapters include sections on Linux®-based system design, model-based simulation, and xPC-Target system design. In these chapters, it contains applications on various real-life systems such as the underwater robotics vehicle, vacuum cleaning, climbing robot for inspection, magnetic levitation for conveyor system, temperature monitoring, face recognition and vision-based inspection using camera, and vibration sensor. As it is not possible to cover every single subject in each chapter, the chapters therefore emphasize on certain topics in the embedded systems design process. The software adopted throughout the chapters are Ubuntu/ Fedora"! Python"! Qt"! MATLAB®/Simulink®, and other open-source software development kits from PIC-Microchip, ARDUINO®, and R